Students’ Levels of Recognition of Parallelogram and of Establishment of Connections - Biber, Abdullah Çağrı; Tuna, Abdulkadir; Kepceoğlu, İbrahim; Kepceoğlu, İbrahim (Sciedu Press, 2019)
In this research, it is aimed to explore how students are able to define parallelogram and to establish relations withother quadrilaterals at each class level comparatively. Case study is chosen as the methodology of this study and theparticipants of the study are 120 middle school students from a state middle school in Turkey. Two open-endedquestions are used to gather data and the descriptive analysis is used. The results of the study show that the studentsdetermine parallelogram based on its typical image. Furthermore, students have not fully grasp the hierarchicalrelation between these special quadrilaterals in their minds.
Keywords: 4. Education